2020
DOI: 10.1111/mam.12199
|View full text |Cite
|
Sign up to set email alerts
|

Footprint tunnels are effective for detecting dormouse species

Abstract: Glirids are arboreal rodents that are difficult to monitor due to their nocturnal activity and their relatively low density. We compared results from footprint tunnels with those from two other monitoring methods (nest boxes and nesting tubes) for three dormouse species in an occupancy framework. Footprint tunnels performed better than the other two methods for the hazel dormouse Muscardinus avellanarius and the edible dormouse Glis glis, and were the only method which detected the garden dormouse Eliomys quer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The differences between this study and the existing literature might be attributed to survey methods. Most of the previous research use natural nests (Berg, 1996; Berg & Berg, 1998; Ramakers et al., 2014; Wolton, 2009) or nest tubes (Chanin & Woods, 2003; Dondina et al., 2016; Ehlers, 2012) to assess hazel dormouse presence, whilst we employed footprint tunnels which have been shown to be faster (Bullion et al., 2018; Mills et al., 2016) and more effective methods of detecting dormice (Melcore et al., 2020). Techniques relying on nests highlight habitats preferred for nesting locations rather than for foraging or dispersal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The differences between this study and the existing literature might be attributed to survey methods. Most of the previous research use natural nests (Berg, 1996; Berg & Berg, 1998; Ramakers et al., 2014; Wolton, 2009) or nest tubes (Chanin & Woods, 2003; Dondina et al., 2016; Ehlers, 2012) to assess hazel dormouse presence, whilst we employed footprint tunnels which have been shown to be faster (Bullion et al., 2018; Mills et al., 2016) and more effective methods of detecting dormice (Melcore et al., 2020). Techniques relying on nests highlight habitats preferred for nesting locations rather than for foraging or dispersal.…”
Section: Discussionmentioning
confidence: 99%
“…Studies so far have employed surveys of natural nests (Berg, 1996; Berg & Berg, 1998; Ramakers et al., 2014; Wolton, 2009) or nest tubes (Chanin & Woods, 2003; Dondina et al., 2016; Ehlers, 2012) to assess presence, which require dormice to reside in the habitat. Instead, we use footprint tunnels which have been shown to be faster (Bullion et al., 2018; Mills et al., 2016) and better for detecting dormice, with five times the occupancy rates from footprint tunnels compared to nest boxes or tubes (Melcore et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Priestley et al (2021) detected dormice in 3 out of 50 tubes within 8 days using this method, whereas a nest was only found in one tube on day 63 suggesting survey efficiency could be increased significantly. Research by Melcore et al (2020) comparing nest boxes, nest tubes and footprint tunnels found the latter to be most effective and these are increasingly used, but, like the eDNA method, require regular checking and so best suited to short-term surveys. The results from the volunteer and professional surveys combined give a time series of data indicating the state of England's dormouse populations, revealing a decline of 70% since 2000 (Wembridge et al, 2023).…”
Section: Current 'Good Practice' Survey Methodsmentioning
confidence: 99%
“…Monitoring of small nocturnal and arboreal rodent species is difficult and has been conducted mostly with indirect techniques (Melcore et al 2020;Mills et al 2016; but see Adamík et al 2019). Concerning indirect techniques, camera-trapping can be superior to the detection of footprints or hair collection for arboreal species because it enables researchers to collect data about the circadian or diel activity with non-invasive methods (Suzuki and Ando 2019).…”
Section: Introductionmentioning
confidence: 99%